2008
DOI: 10.7863/jum.2008.27.10.1407
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Appearance of Trigger Fingers

Abstract: Thickening and hyper-vascularization of the A1 pulley are the hallmarks of trigger fingers on sonography. Other frequently observed features include distal flexor tendinosis and tenosynovitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 10 publications
5
93
3
Order By: Relevance
“…The A1 pulley is the most important in this condition because not only is it a stabilizer of the flexor tendons during finger flexion, but it also plays a role in the pathogenesis of the trigger finger. 11,12 Tenosynovitis, tendinitis, and cysts of the flexor tendon sheath (ie, ganglia) have been described on sonography in patients with triggering symptoms, but some investigators also observed fibrocartilaginous metaplasia within the inner layer of the A1 pulley. 12 The pulley system has also been evaluated with magnetic resonance imaging and computed tomography, 14 but we choose high-resolution sonography for its higher spatial resolution, the possibility to take reliable quantitative measurements, 12 and better patient acceptance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A1 pulley is the most important in this condition because not only is it a stabilizer of the flexor tendons during finger flexion, but it also plays a role in the pathogenesis of the trigger finger. 11,12 Tenosynovitis, tendinitis, and cysts of the flexor tendon sheath (ie, ganglia) have been described on sonography in patients with triggering symptoms, but some investigators also observed fibrocartilaginous metaplasia within the inner layer of the A1 pulley. 12 The pulley system has also been evaluated with magnetic resonance imaging and computed tomography, 14 but we choose high-resolution sonography for its higher spatial resolution, the possibility to take reliable quantitative measurements, 12 and better patient acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been used previously. 11 On sonography, the hallmarks of a trigger finger as reported by Guerini et al 12 were investigated: thickening of the A1 pulley measured in millimeters in the center of the pulley on axial scans and distal flexor tendinosis (defined as segmental swelling of the flexor tendons) and tenosynovitis (hypoechoic or anechoic thickened tissue with or without fluid within the tendon sheath, which is seen in 2 perpendicular planes and may show a Doppler signal).…”
Section: Clinical Examination and Sonographic Studiesmentioning
confidence: 99%
“…However, increasingly, high-resolution US imaging is being used to complement the clinical assessment in the diagnosis and management of trigger fingers. It allows the direct visualization of the A1 pulley-flexor tendon complex in cases of flexor tendon involvement [6,[9][10][11]. US can show combination of findings including thickening, hypoechogenecity and hyper-vascularization of A1 pulley that overlies the metacarpal heads, alteration in echotexture of the flexor tendons that pass through the digital tunnel and synovial sheath effusion around the tendons [6,[9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Only few case reports describe the impingement of an extensor tendon within the extensor retinaculum (ER) resulting in trigger [3][4][5]. There are a few reports on sonographic evaluation of trigger fingers describing only about the flexor tendon involvement [6]. We have not come across any report in the literature on real-time ultrasound (US) imaging in the diagnosis of extensor tendon triggering.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although occupational therapy practitioners often equate trigger finger with swelling of the involved flexor tendon, sonographic data have indicated that fewer than half of people with trigger finger have tendonopathy (Guerini et al, 2008). Instead, regardless of the presence of tendonopathy, nearly all people with trigger finger have a thickened pulley, limiting tendon gliding (Guerini et al, 2008;Sato, Ishii, Noguchi, & Takeda, 2012).…”
Section: Clinical Reasoningmentioning
confidence: 99%